2017
DOI: 10.1038/s41598-017-00135-6
|View full text |Cite
|
Sign up to set email alerts
|

De novo [PSI +] prion formation involves multiple pathways to form infectious oligomers

Abstract: Prion and other neurodegenerative diseases are associated with misfolded protein assemblies called amyloid. Research has begun to uncover common mechanisms underlying transmission of amyloids, yet how amyloids form in vivo is still unclear. Here, we take advantage of the yeast prion, [PSI +], to uncover the early steps of amyloid formation in vivo. [PSI +] is the prion form of the Sup35 protein. While [PSI +] formation is quite rare, the prion can be greatly induced by overexpression of the prion domain of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 70 publications
0
47
0
Order By: Relevance
“…Sup35PrD-GFP was overexpressed to induce the formation of fluorescent aggregates, such as early foci and rings, while observing Cof1-RFP localization. Capturing early foci is difficult because of their transient nature (Sharma et al, 2017) yet our observations of the few early foci containing cells obtained did not show any clear examples of colocalization between Sup35PrD-GFP and Cof1-RFP ( Fig 1A). In ring containing cells, we did notice overlap between Sup35PrD rings and Cof1-RFP foci in 'flattened' whole cell images.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Sup35PrD-GFP was overexpressed to induce the formation of fluorescent aggregates, such as early foci and rings, while observing Cof1-RFP localization. Capturing early foci is difficult because of their transient nature (Sharma et al, 2017) yet our observations of the few early foci containing cells obtained did not show any clear examples of colocalization between Sup35PrD-GFP and Cof1-RFP ( Fig 1A). In ring containing cells, we did notice overlap between Sup35PrD rings and Cof1-RFP foci in 'flattened' whole cell images.…”
Section: Resultsmentioning
confidence: 80%
“…Alternatively, since we previously showed that 50% of cells containing dots are not viable (Sharma et al, 2017), the formation of dot structures in act1-120 may be more toxic than in wildtype cells.…”
Section: Actin Patch Polarization Is Not Required For Prion Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once residing at the periphery, the majority of the diffuse Sup35NM quickly converges into the aggregate within 20 min. This quick sequestration coincides with the growth of the aggregate into dots, or ring-and line-like structures (Sharma et al, 2017;Zhou, Derkatch, & Liebman, 2001). Cells containing these structures are considered to be hallmarks of [PSI + ] because cells that contain aggregates give rise to [PSI + ] cells but diffuse cells do not (Ganusova et al, 2006;Sharma et al, 2017).…”
Section: Sup35p As a Prionmentioning
confidence: 99%